Early systematic communication between physician, patient and employer to promote return to work. (30th September 2020) - Nordling, P; Nordeman, L; Skoglund, I M; Björkelund, C; Hensing, G
Abstract: Background: In the sickness absence and return-to-work process communication between stakeholders is beneficial but difficult to achieve. Addressing work-related issues early in the process could support decision making. The aim of this study was to test if early systematic communication about work and health between physician, patient/employee and employer facilitated by a communication tool, the Capacity Note, was feasible for patients with common mental disorders (CMD) in primary care. Methods: In a pragmatic trial, physicians at primary health care centers (PHCCs) were randomized to control/intervention physician and were responsible for identifying eligible patients. In addition to usual care, intervention patients used the Capacity Note with their physician and were then instructed to use it with their employer and return it to the physician. Control patients received usual care. A study log book and sick leave data for each PHCC were used for process evaluation purposes. Results: Eighteen of 24 PHCCs in the region were contacted; eight participated. At study start, 434 patients filled the basic inclusion criteria. Of these, 93 were identified as eligible by the physicians and were asked to participate. Around 40% declined participation, most commonly due to lack of energy or hesitation to talk to the employer. The final sample included 56 patients. Of the 28 intervention patients nine (32%) completed the intervention. Conclusions: The study was negatively affected by suboptimal research conditions in primary care (e.g. severe time constraints). Also, the patients' hesitation to participate highlights the sensitivity of the topic and the difficulties in doing research in this vulnerable patient group. Thus, the feasibility was hampered by both organizational and patient related factors. It is of utmost importance to improve possibilities for social psychiatric research in primary care given the high prevalence of CMD and associated reduced capacity to work. Key messages: Discussing health-related issues with the employer was seen as a sensitive matter among patients with common mental disorders. Research on best practices for sickness certification and return-to-work was difficult to achieve due to both personal and organizational factors.